Efisiensi Teknis Usahatani Kubis Petani di Kabupaten Karo - Esra Frandika Karo-Karo; Dominicus Savio Priyarsono; Sri Hartoyo (Jurnal Agro Ekonomi, 2021)
EnglishKaro Regency is the center of cabbage production in North Sumatra Province. The cabbage farming productivity in North Sumatra Province is low compared to other provinces on the island of Sumatra. This study aims to evaluate the cabbage farmings economic feasibility and technical efficiency. Farming feasibility was evaluated financially whereas technical eficiency was measured using the stochastic Cobb-Douglas production function in two categories, marginal and non-marginal farmings. The data was collected through a survey in February-June 2020 with respondents of 58 farmers for each categories. The results showed that the marginal farmings were technically efficient but were not profitable if land rent and labor cost were inputed. In contrary, the non-marginal farmings were technically inefficient but were profitable. This indicates that the poor but efficient hypothesis is true. The significant determinants of of the marginal farmings technical inefficiency were farmer’s age, labor ratio, land ownership, and farmer group membership. The study failed to find any significant determinant of technical inefficiency of the non-marginal farmers. The techical efficiency and profitablity of the cabbage farmings could possibly increased by increasing farmers’ participation in farmers group, building irrigation, developing agricultural institutions and trainings on good seedling practices.IndonesianKabupaten Karo adalah sentra utama produksi kubis di Provinsi Sumatera Utara. Tingkat produktivitas usaha tani kubis di Provinsi Sumatera Utara relatif rendah dibandingkan provinsi lainnya di Pulau Sumatera. Penelitian ini bertujuan untuk mengevaluasi kelayakan ekonomi dan efisiensi teknis usaha tani kubis. Kelayakan usaha dianalisis secara finansial, sedangkan efisiensi teknis diukur dengan fungsi produksi Cobb-Douglas stokastik dalam dua kategori usaha tani, yaitu petani gurem dan bukan gurem. Data dikumpulkan melalui survei pada Februari–Juni 2020 dengan responden 58 petani untuk setiap kategori yang dipilih purposif. Penelitian menunjukkan bahwa usaha tani kubis skala gurem efisien secara teknis namun tidak menguntungkan jika biaya tenaga kerja keluarga dan sewa lahan diperhitungkan. Sebaliknya, usaha tani kubis berskala bukan gurem tidak efisien secara teknis namun menguntungkan secara finansial. Artinya, hipotesis ‘poor but efficient’ berlaku. Faktor-faktor yang berpengaruh terhadap inefisiensi teknis usaha tani gurem hingga tingkat nyata 10% adalah usia petani, rasio tenaga kerja, status lahan, anggota kelompok tani, sedangkan untuk usaha tani bukan gurem tidak ditemukan faktor-faktor sosial ekonomi yang memengaruhi efisiensi teknis hingga tingkat nyata 10%. Efisiensi teknis dan pendapatan usaha tani kubis masih dapat ditingkatkan dengan meningkatkan partisipasi petani dalam kelompok tani, membangun saluran irigasi, memfasilitasi tumbuh kembangnya lembaga pertanian dan memberikan pelatihan menyemai bibit yang baik.